A Bread Wheat Line with the Substituted Wild Emmer Chromosome 4A Results in Fragment Deletions of Chromosome 4B and Weak Plants - Yu Qiu; Fei Lu; Bohao Yang; Xin Hu; Yanhao Zhao; Mingquan Ding; Lei Yang; Junkang Rong (Plants)
In response to the growing genetic uniformity within wheat populations, developing efficient wheat–alien translocation strategies has become critically important. We observed that several offspring of the common wheat (Triticum aestivum L.)–wild emmer (Triticum turgidum L. var. dicoccoides) chromosome arm substitution line (CASL4AL) exhibited stunted growth, including significantly reduced plant height, spike length, spikelet number, and stem width compared to normal plants. Integrative transcriptomic analyses (RNA-Seq and BSR-Seq) revealed a statistically significant depletion (p < 0.01) of single nucleotide polymorphisms (SNPs) on chromosome 4B in compromised plants. Chromosome association analysis of differentially expressed genes (DEGs, up- or downregulated) revealed that downregulated genes were predominantly located on chromosome 4B. The 1244 downregulated DEGs on Chr4B were employed for Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses, and RNA metabolic processes, DNA repair, and transport systems were significantly enriched by GO analysis; however, only the mRNA surveillance pathway was enriched by KEGG enrichment. Molecular marker profiling showed a complete absence of target amplification in the critical 0–155 Mb region of chromosome 4B in all weak plants. Pearson’s correlation coefficients confirmed significant associations (p < 0.01) between 4B-specific amplification and weak phenotypes. These results demonstrate that 4B segmental deletions drive weak phenotypes in CASL4AL progeny, and provide experimental evidence for chromosome deletions induced in wild emmer chromosome substitution lines. This study highlights the potential of wild emmer as a valuable tool for generating chromosomal variations in wheat breeding programs.